(untitled) (Journal of Applied Oral Science, 2010)
Esthetics and durability of materials used to fabricate artificial eyes has been an important issue since artificial eyes are essential to restore esthetics and function, protect the remaining tissues and help with patients' psychological therapy. However, these materials are submitted to degrading effects of environmental agents on the physical properties of the acrylic resin. OBJECTIVE: This study assessed the color stability of acrylic resins used to fabricate sclera in three basic shades (N1, N2 and N3) when subjected to accelerated aging, mechanical and chemical polishing. MATERIAL AND METHODS: Specimens of each resin were fabricated and submitted to mechanical and chemical polishing. Chromatic analysis was performed before and after accelerated aging through ultraviolet reflection spectrophotometry. RESULTS: All specimens revealed color alteration following polishing and accelerated aging. The resins presented statistically significant chromatic alteration (p